Discrete uniform limit law for additive functions on shifted primes - Stepanauskas, Gediminas; Žvinytė, Laura (Nonlinear Analysis: Modelling and Control, 2016)
The sufficient and necessary conditions for a weak convergence of distributions of a set of strongly additive functions fx , x ⩾ 2, the arguments of which run through shifted primes, to the discrete uniform law are obtained. The case when fx (p) ∈ 0, 1 for every prime pis considered.